Islamic Chinese Art: Islamic anthology of Chinese calligraphy - Maryam Mohammed Al-Mannai (20362764) (2021)
When Islam spread from the Arabian Peninsula to the rest of the world, it impacted the lives of millions of people. One of the impacts was related to the influence on art, especially when Islam entered China in the 7th century. The Chinese Islamic art was a challenging product due to two major factors. The first factor was that the transition of traditional Arabic calligraphy to Chinese Arabic calligraphy was not straightforward due to the huge difference in how Arabic letters and Chinese characters are displayed. The second factor was related to the translation because the Chinese language uses characters to explain the intended meaning, whereas the Arabic language is an expressive and specific language. This paper provides examples of Chinese Islamic art where errors have been observed in written verses from Qur'an or even in spelling the names of Allah. Moreover, it provides interesting examples of pottery and porcelain pieces that were found and preserved in Qatar Museum as well as in Al-Zubara Fort. Other Information Published in: QScience Connect License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/connect.2021.3